Attitude towards reflection in teachers in training. Issue 3 (3rd May 2020) - Nocetti, Alejandra; Otondo, Maite; Contreras, Gladys; Pérez, Cristhian
ABSTRACT: In Chile, writing, dialogue and observation are used to stimulate reflection among teachers in training. The lack of research on the relationship between the impact of these strategies and the development of a positive attitude toward reflection poses a problem. Therefore, the objective of this study is to analyze whether carrying out the Reflective Teaching Learning Cycle (CRAD for its acronym in Spanish) is associated with changes in attitude toward teacher reflection. A quantitative methodology with a pre-experimental scope is used. The results show an increase in favorable conceptions of reflection and a greater affective willingness towards examining their own interventions. They understood that reflecting means recognizing assumptions of the teaching action and the consequences that they have on the students' learning and formation. It is concluded that carrying out CRAD is positive in terms of stimulating teaching reflection. However, further studies are required in order to measure the effectiveness of this work model.